Save Time up to 50% with Truline Binder - Hercules Incorporated (1943 Hercules Advertisements, 1943)
Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Chemical industry; Foundries; Hercules Incorporated; Corporations; Naval stores; Founding; Metal castings; Advertising, Industrial